نظام الحصص الاستيراد في الجزائر - وليد, بكاكرة; جمال, بوزيدي (جامعة الوادي - University of Eloued, 2023)
"لجأت الجزائر لنظام الرخص لمعالجة انعكاسات الأزمة الاقتصادية العالمية ، حيث وأن كان النظام يتعارض مع مبدأ حرية الصناعة والاستثمار، ويتعارض مع أحكام اتفاق الشراكة المبرم بين الطرف الأوربي والجزائري وذلك تطبيقا لنص المادة 17من الاتفاق إلا أن نظام الحصص والقيود الكمية الأخرة التي تبناها المشرع بهدف حماية الاقتصاد الوطني تجد مببرها القانوني في نص المادة 11من اتفاق الجات اسنة 1994التي سمحت بلجوء الأطراف للقيود الكمية لمعالجة خلل في ميزان المدفوعات. حيث تبنى المشرع نوعين من الرخص الرخص التلقائية والرخص غير التلقائية وذلك للحد من نزيف العملة وتآكل احتياطي الصرف لا يمكن لنظام الرخص وحده أن يعالج عجز ميزان صادرات بلغ 46.7ملياردولار نهاية سنة .2016 و و خفض الواردات التي بلغت قيمتها حوالي 45مليار دولار سنة ،2017." "Algeria resorted to the licensing system to deal with the repercussions of the global economic crisis It contradicts the principle of freedom of industry and investment, and contradicts the provisions of the partnership agreement concluded between the parties European and Algerian, in application of the text of Article 17 of the agreement, but the system of quotas and other quantitative restrictions Adopted by the legislator with the aim of protecting the national economy, it finds its legal justification in the text of Article 11 of the agreement GATT in 1994, which allowed the parties to resort to quantitative restrictions to address an imbalance in the balance of payments. where The legislator adopted two types of licenses, automatic licenses and non-automatic licenses, in order to reduce currency bleeding And the erosion of exchange reserves, the licensing system alone cannot address the deficit in the balance of exports, which amounted to 46.7 billion dollars at the end of 2016. And reduce imports, which amounted to about 45 billion dollars in 2017."
Keywords: نظام الحصص، للاستيراد، الجزائر; Quotas. System